São Gonçalo da Mussuca em transformação: os impactos causados por festivais culturais em grupos populares - Santos, Denisson Cleber de Farias (2022)
The present research approaches the transformations that permeate the group São Gonçalo da Mussuca, driven by cultural festivals. This work aims to demonstrate, besides São Gonçalo, how cultural events affect traditional groups. The study follows an ethnomusicologic bias, dealing with musical aspects as a vector of change and the festivals as catalyzing spaces. To better structure these issues, the work is divided into three parts. The first part presents the historical processes of the event and internal transformations; the second part addresses the external conditions, represented by the implications brought about by the festivals; and the third part analyzes the effects caused by these implications. The methodological resources that the research uses are part of a qualitative approach, with an analytical base in ethnomusicology, using data obtained in field and analysis of audiovisual, documental and bibliographic material. In conclusion, the study justifies how certain changes arise and are established, which mark the evolutionary process that popular culture groups have been going through.